2012
DOI: 10.1259/dmfr/86834844
|View full text |Cite
|
Sign up to set email alerts
|

Osteosarcoma of the jaws: demographic and CT imaging features

Abstract: Objective: The aim of this study was to evaluate the patient demographic and CT imaging findings of primary osteosarcoma of the jaws. Methods: 88 primary osteosarcomas of the jaws histopathologically diagnosed during 1997-2007 were reviewed. 21 cases of CT images were reviewed. Results: Of 88 patients, 51 (58%) had tumours in the mandible and 37 (42%) in the maxilla. The mean age was 37.8 years (range 9-80 years). The male-to-female ratio was 1.32:1. The mean age of patients with mandibular lesions was 41.04 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(31 citation statements)
references
References 9 publications
3
27
0
1
Order By: Relevance
“…In certain cases, the typical 'sunray' appearance may be observed at the periphery of the tumor in plain radiographs and computed tomography scans. The hallmark of cementoblastoma is the sharp border between the tubular dentin of the root and the cementum-like A B component (15). In the present case, the osteosarcoma resembling cementoblastoma mimicked 'benign' bone growth, and there was no observation of the typical 'sunray' radiographical appearance.…”
Section: Discussionmentioning
confidence: 41%
“…In certain cases, the typical 'sunray' appearance may be observed at the periphery of the tumor in plain radiographs and computed tomography scans. The hallmark of cementoblastoma is the sharp border between the tubular dentin of the root and the cementum-like A B component (15). In the present case, the osteosarcoma resembling cementoblastoma mimicked 'benign' bone growth, and there was no observation of the typical 'sunray' radiographical appearance.…”
Section: Discussionmentioning
confidence: 41%
“…Osteosarcoma of the jaw is associated with certain specific characteristics, such as a higher prevalence in the maxilla and male predominance. Wang et al reported that all maxillary de novo osteosarcomas arose from the alveolar ridge (5). The mass in the present case involved both the alveolar ridge and the body of the maxilla, possibly due to long-term growth leading to extension of the mass from the alveolar ridge to the body.…”
Section: Discussionmentioning
confidence: 58%
“…OSJ occurs in the mean age range of 31-40 years (5,6) with a debatable gender predilection. Some studies have reported male predominance (7) whereas some have reported female predominance (8) and equal gender distribution.…”
Section: Discussionmentioning
confidence: 99%